The Tradition Of Recording And Preserving Manuscripts In China - Nurni W. Wuryandari (Bambuti, 2022)
China can be called a country with a consistent attitude in recording various events. Conditions and figures that are considered essential. Besides having a strong tradition of taking notes, China also has a habit of trying to preserve records. One of the crucial figures who contributed to the preservation of the manuscript was the emperor Qian Long (1736-1796), one of the emperors during the Qing dynasty (1644-1911). He collected valuable and rare books into a series of publications called Siku Quanshu (四庫全書), which is often referred to as the Imperial Collection of Four. In addition to collecting various information about their own country, Siku Quanshu also gathers information about other countries, including the Archipelago. This short paper aims to introduce the tradition of note-taking and the efforts to preserve manuscripts carried out in China, along with its benefits for researchers in China and foreign. Good Chinese language skills are the decisive key to penetrating the collection of knowledge stored in these precious Chinese manuscripts.